Comparing Solved and Unsolved No-Body Homicides in Australia: An Exploratory Analysis. Issue 4 (November 2019) - Ferguson, Claire; Pooley, Kamarah
Factors that are both within and outside of police discretion can pose challenges to solving homicides generally. There has been little study of no-body homicides, nor why some remain unresolved. This analysis compares solved and unsolved no-body homicides in Australia using Pearson's chi-square tests of independence. Coroners' findings, case law, and media reports from 1983 to 2017 were examined. Cases ( N = 55; 42.4% solved) differed based on the victim's age, who reported them missing, reward money, Coronial inquests, who determined homicide, availability of evidence and confessions, suspects lying, establishing crime scenes, and motivations.